Assessing Cross-Sector Stakeholder Perspectives on Oakland (CA)'s Juvenile Reentry System. (December 2017) - Jain-Aghi, Sonia; Cohen, Alison K.; Jagannathan, Priya; Bassey, Henrissa; Leung, Yvette; Alley-Caliz, Marthea; Bedford, Sara
We surveyed 75 staff and administrators involved in Oakland (CA)'s Second Chance Initiative from diverse agencies (e.g., probation, behavioral health, public health/medical, education, community-based service providers) to assess the local juvenile reentry system. Sharing and using data across partner agencies, mutual trust, opportunities for interagency collaboration, system-level youth and family engagement, shared governance, and limited resources repeatedly arose as areas for improvement. Many defined reentry success using positive youth developmental outcomes. Government and community perspectives around barriers and effectiveness often differed with some similarities.